The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1111/jocs.14116
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary trends and outcomes of mitral valve surgery for infective endocarditis

Abstract: Background Contemporary data on mitral valve (MV) surgery in patients with infective endocarditis (IE) are limited. Methods The National Inpatient Sample was queried to identify patients with IE who underwent MV surgery between 2003 and 2016. We assessed (a) temporal trends in the incidence of MV surgery for IE, (b) morbidity, mortality, and cost of MV repair vs replacement, and (c) predictors of in‐hospital mortality. Results The proportion of MV operations involving patients with IE increased from 5.4% in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The current study presents a 15-year experience in a high-volume single-centre comparing the long-term outcomes of MVr and MVR in native valve endocarditis. As a specialist centre, we found that MVr was feasible in 46% of patients, higher than numerous contemporary studies [9,10,16,17]. Patients unsuitable for MVr were more likely to be higher risk (higher logistic EuroSCORE, non-elective, active IE).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The current study presents a 15-year experience in a high-volume single-centre comparing the long-term outcomes of MVr and MVR in native valve endocarditis. As a specialist centre, we found that MVr was feasible in 46% of patients, higher than numerous contemporary studies [9,10,16,17]. Patients unsuitable for MVr were more likely to be higher risk (higher logistic EuroSCORE, non-elective, active IE).…”
Section: Discussionmentioning
confidence: 64%
“…Despite these clear recommendations, MVr rates have lagged. The National Inpatient Sample in the USA report a repair rate of 25% [9] and the Taiwan National Health Insurance program report a repair rate of 21% [10]. This could be due to concerns over the durability of MVr and recurrence of IE especially in active endocarditis and in non-elective surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these potential limitations, a major strength of our study is that rather than relying solely on ICD codes as multiple prior studies have done [6,9,20,29,30], we validated IE and drug use diagnoses with other clinical indicators through a detailed chart review. Use of ICD code combinations for identification of DU-IE are not specific and frequently fail to identify DU-IE cases correctly [31].…”
Section: Plos Onementioning
confidence: 99%
“…In the last decade, the number of patients with IE undergoing MV surgery has increased significantly as well as the number of mitral valve repair [18] . However, the percentage of repair vs. replacement showed high variability in different centers.…”
Section: The Endocarditis Team -Rolementioning
confidence: 99%